Müsteri ilişkileri yönetiminin finans sektöründeki yeri ve önemi - Torun, Açelya (My University, 2004)
Customer Relationship Management, CRM is to connect to customers in long term and maximize their profit. In other words CRM is to focus to the customers not to products, and by this way to answer the customers’ needs. The only way to make this possible is to know the current and potential customers. So, it is possible to gain “good” customers and make them loyal for your company and to convert “bad” customers to good customers or to keep them away from the company. CRM, first of all is to know the truth about gaining new customers is harder than keeping the current customers in the firm. According to the statistics about this subject, to find a new customer is 3 to 9 times more expensive than to keep the current customer in the firm. For example, to gain a new customer with Internet marketing costs 34 USD, on the contrary it is only 6.80 USD to keep the current customer. An increase by 5 % in the ratios of customer holding, results in an increase about 20 % to 95 % in profits. In finance sector it is easier to apply CRM and results in more profits, which is different from other sectors. In non-finance sectors the cost to gain new customers is 3 or 4 times more expensive than keeping the current customers, which can be 10 times more expensive in finance sector. The aim of CRM in finance sector is to focus on the customers that are profitable or has a potential to be profitable and understand their requirements. With this study, CRM and CRM in finance sector has been tried to be explained.
Keywords: Yönetim